Discrimination of phosgene from cyanogen chloride in recovered chemical munitions using tagged neutron interrogation with high-resolution gamma-ray spectroscopy. (February 2023) - Bucher, B.; Seabury, E.H.; Hix, J.; Krebs, K.M.; Wharton, C.J.; McConchie, S.M.; Hausladen, P.A.
Abstract: The associated particle (AP) technique has recently been used with a high-purity germanium γ -ray spectrometer to assess its capability to improve field identification of recovered chemical warfare (CW) materiel through prompt gamma-ray neutron activation analysis (PGNAA) measurements. A particularly challenging pair of CW agents commonly found in recovered munitions are phosgene (CG) and cyanogen chloride (CK), which have two of three elements in common, i.e. chlorine and carbon, but differ in the third being either oxygen or nitrogen. The detection of both latter elements is complicated by high oxygen concentration in the field environment which interferes with the small signal produced from the chemical agents. The matter is further complicated by the precautionary field practice of overpacking recovered munitions with vermiculite in larger steel multiple round containers (MRCs), which places additional oxygen-rich material in contact with the munition while further attenuating an already weak signal emitted from the munition center. This work reports quantitative results from realistic field measurements of CG and CK simulants in mock 4.2-inch (11 cm) mortar rounds overpacked with vermiculite in a large MRC. Results obtained with the AP technique are compared to those obtained with the traditional PGNAA approach for both overpacked- and bare-munition measurements. The AP technique is shown to provide a much more confident discrimination between the two chemicals, particularly for the more challenging field-relevant overpacked measurements, where a significant gain in sensitivity to all the key elements (chlorine, carbon, nitrogen and oxygen) is achieved. Highlights: Associated Particle (AP) technique allows better discrimination between phosgene and cyanogen chloride in recovered chemical munitions. Improved prompt gamma-ray neutron activation analysis (PGNAA) sensitivity to key elements C, N, O, and Cl with AP technique. Achieved success for field-relevant measurements of overpacked munitions in multiple round containers (MRCs). Strong suppression of background oxygen enables better discriminability and sensitivity.